Victims of work accident's description in an emergency unit in southern Brazil - Josemar Batista; Suzane Cristina Rodrigues; Tarcisio Vitor Augusto Lordani; Rafaela Andolhe (Universidade Federal de Santa Maria, 2015)
Aim: to investigate the description of the victims of work accidents treated at an Emergency Unit (UPA) in southern Brazil. Method: descriptive, cross-sectional survey with documentary analysis and quantitative approach used on data collected in 391 medical records selected by time frame from January to June 2012. Data were submitted to descriptive statistics. Results: most typically, the majority of accidents had male victims, with ages from 20 to 39 and involved the agribusiness sector. Concerning the nature of the lesions, the majority of them was the blunt cut wounds and bruises having fingers/ feet as the most affected regions. The highest absence time from work was reported between 1-3 days. Conclusion: the description of the victims of work accidents treated at an UPA provides subsidies for the development and supervision of accident prevention programs, as well as the guidance of the nursing action